A triple bottom line assessment of concentrated solar power generation in China and Europe 2020–2050. (October 2022) - Hahn Menacho, A.J.; Rodrigues, J.F.D.; Behrens, P.
Abstract: Concentrated solar power (CSP) can be a flexible renewable resource on electric grids. Here we assess the direct and upstream socio-economic and environmental impacts of the projected deployment of CSP in China and Europe, using Input-Output Analysis. We first quantify the CSP experience curve, finding a learning rate of ∼16%, and combine this with future projections for installed capacity from China's National Development and Reform Commission and the International Energy Agency. We find employment intensities of 4.2 and 2.3 person-year/GWh in China and Europe, respectively (higher than PV and wind). The carbon emission intensity of CSP is currently higher than alternatives but this gap may narrow through learning. Carbon intensities are estimated at 129.7 and 99.8 gCO2eq/kWh in 2020 (in China and Europe, respectively) and could drop to 40.4 and 31.1 gCO2eq/kWh by 2050 given the projected expansion. We discuss the importance of including both environmental and socio-economic dimensions when assessing the impact of energy technologies and provide context for the role of CSP in the energy transition. Highlights: Environmental, economic, and social impact assessment of concentrated solar power. Carbon intensities of 129.7 and 99.8 gCO2eq/kWh for China and Europe. Employment intensities of 4.2 and 2.3 person-year/GWh in China and Europe. Learning rate is calculated at ∼16%. Future cost scenarios show high CSP potential in some regions.